Iron-Catalyzed C(sp3)–H Alkylation through Ligand-to-Metal Charge Transfer - Kang, Yi Cheng; Treacy, Sean M.; Rovis, Tomislav (Synlett, 2021)
We report the FeCl3-catalyzed alkylation of nonactivated C(sp3)–H bonds. Photoinduced ligand-to-metal charge transfer at the iron center generates chlorine radicals that then preferentially abstract hydrogen atoms from electron-rich C(sp3)–H bonds distal to electron-withdrawing functional groups. The resultant alkyl radicals are trapped by electron-deficient olefins, and the catalytic cycle is closed by Fe(II) recombination and protodemetalation.
Keywords: C(sp3)–H bond activation; photocatalysis; charge transfer; iron catalysis; alkylation; alkenes